ChemInform Abstract: A Facile Synthesis of Annulated Azolo[c][1, 2, 4]thiadiazine S, S‐Dioxides. Issue 23 (16th May 2013) - Cherepakha, Artem; Kovtunenko, Vladimir O.; Tolmachev, Andrey
Abstract Base‐mediated condensations of halogenated substrates (I) with 3‐aminoazoles provide directly the biologically important title scaffold in a one‐pot manner.